Peer relationship, family factors, and mental health in rural children: a network analysis - Huang, Zhen-Xing; Li, Hao-Ming (Frontiers in Psychiatry, 2025)
The transition from childhood to early adolescence is a critical developmental period, particularly in rural areas where unique factors play a significant role. This study examined the interplay of peer and family factors on the mental health, including anxiety and depression, of 694 rural Chinese children in the transition to adolescence (aged 10-14). This study employed a quantitative design, analyzing data from 16 rural schools across seven provinces using Mixed Graphical Model (MGM) and Gaussian Graphical Model (GGM) network analyses to explore the relationships between variables related to family factors, peer relationships, anxiety, depression, and behavioral problems. Network analysis revealed that depression was a central node, and peer relationships had a greater impact on the mental health of these children than family factors. There was a significant correlation between depression and anxiety (weight = 0.55). Peer relationships were negatively associated with depression (weight = -0.31) and positively associated with father involvement. In contrast, the network shows that the experience of being left behind was not directly associated with mental health outcomes. Further analysis of the depression network revealed that negative mood was a central node. This study highlights that peer relationships have a far stronger connection to the mental health of rural Chinese children than family factors. Depression, and specifically negative mood, was central to the network, emphasizing the need for interventions that focus on improving peer interactions and addressing core depressive symptoms.